“Tudo é violência, viver é violência”: representações sociais de mulheres em situação de rua na Regional Centro-Sul de Belo Horizonte/mg sobre violência - Sergio Rosa Neves Temponi (2020)
The multiple faces of violence and its impact on the health of populations are also evident and present themselves on the scene of homeless people, including in large cities. This phenomenon has become a public health problem and an urgent one in promoting and protecting citizenship of vulnerable populations. Public policies add up to efforts that are evident with intersectoral articulation and other agendas. However, the number of homeless people in Belo Horizonte is increasing every day. Women who are in this situation are in very peculiar conditions of violation of rights. The objective of this research was to identify the social representation (s) of homeless women in the central-south region of Belo Horizonte on violence, in view of their own condition of vulnerability, by the representation that they have of themselves and their condition of life on the streets. The methodology was guided by qualitative research with the application of a structured questionnaire to 22 women and by 3 semi-structured narrative interviews. The analysis of the representations produced by the speeches and reports of the experiences of women living on the street, these data through content analysis combined with the lexical analysis, in addition to the analysis of trajectories. Such data analysis proposed to answer the hypotheses of women's organization, individual strength, their representations about life on the street and how this composes their experience about violence. Through the interviews, it can be seen that at least 75% of the women interviewed are migrants, who came to the capital to improve their conditions of existence, with a trajectory of intrafamily or domestic violence. It was considered that the social representations of cisgender and transgender women living on the streets are very similar, although they experience different strategies to deal with the vulnerabilities posed by their exposure to street violence. Thus, this dissertation sought to contribute to the instrumentalization and delineation of interventional practices and methodological alignments for the work processes of teams, programs and services that access street users from the constructions identified by the users of these social assistance services, becoming essential to public policies, also expanding the understanding of the reception and more assertive forms of intervention, based on secured security and human rights and citizenship.